Reactions to supply chain disruptions: Evidence from German firms - Cevat Giray Aksoy; Andreas Baur; Lisandra Flach; Beata K. Smarzynska Javorcik (CESifo GmbH, 2022)
Since the outbreak of the Covid-19 pandemic, the configuration of international supply chains has received increased public attention. Pandemic-related disruptions in production and transportation have led to questions about the reliability of international production networks. Moreover, the war in Ukraine and the associated sanctions against Russia have cast a new light on the geopolitical significance of economic interdependencies with autocratic regimes. How do firms react to these developments, and have they already adjusted their sourcing strategies? In this policy brief, we present the results from a representative survey of more than 4,000 firms in Germany, providing insights into how companies have responded to supply chain disruptions and which priorities they are setting for the future.
Keywords: 330